Lipid profiles in smoking and non-smoking male adolescents - Prastyanto, Sigit; Sitaresmi, Mei Neni; Julia, Madarina (Paediatrica Indonesiana, 2014)
Background The prevalence of smoking in adolescents tends to increase. Smoking is associated with a higher risk of dyslipidemia. Objective To compare the lipid profiles of tobacco-smoking and non-tobacco-smoking male adolescents. Methods We performed a cross- sectional study in three vocational high schools in Yogyakarta from January to April 2011. Data on smoking status, duration of smoking and number cigarettes consumed per day were collected by questionnaires. We randomly selected 50 male smokers and 50 male non-smokers as the study subjects. Results Mean differences between smokers and non-smokers were 44.5 (95%CI 28. 7 to 60.1) mg/dL for triglyceride levels; 8.0 (95% CI 1.0 to 14.9) mg/dL for low density lipoprotein (LDL) cholesterol; 11.8 (1.1 to 22.4) mg/dL for total cholesterol and -5.7 mg/dL (95% CI -8.8 to -2.6) for high density lipoprotein (HDL) cholesterol. Mean differences (95% CI) between smokers who had engaged in smoking for > 2 years and those who had smoked for :S:2 years were -18.1 (95% CI -33 .9 to -2.3) mg/dL for total cholesterol; -49.4 (95% CI -67.2 to -3 1.5) mg/dL for triglycerides. Mean differences between those who smoked > 5 cigarettes/day and :s:5 cigarettes per day were -18 .4 (95% CI -32.8 to -4.1) mg/ dL for total cholesterol and -29.1 (95% CI -53.6 to -4.6) mg/dL for triglycerides. Conclusion Smoking more than 5 cigarettes/day significantly increases total cholesterol, LDL cholesterol, and triglyceride levels, as well as reduces HDL cholesterol levels; while smoking more than 2 years significantly increases total cholesterol and triglyceride levels